APPLICATION OF THINK PAIR SHARE (TPS) MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN PANCASILA AND STATE EDUCATION (PPKN) LESSONS (IN MTS HIDAYATUS SHIBYAN PARIT NA’IM KABUPATEN KUBU RAYA) - Syaifurrahman, Syaifurrahman; Rosyid, Sulistyarini; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this research is "Application of Think Pair Share Learning Models to Improve Learning Outcomes of PPKn Students in Class VII Semester I MTS Hidayatus Sibyan 2017/2018 Academic Year. The purpose of this class action research was. 1) Applying the think pair share learning model to improve the learning outcomes of students. 2) Increasing the absorptive capacity of students in the PPKn learning eye for MTS Hidayatus Sibyan VII class with the implementation of the think pair share model.3) improving student learning outcomes in the learning eyes of class VII PPKn MTS Hidayatus Sibyan. This Classroom Action Research was conducted on students of Class VII Semester I MTS Hidayatussibyan 2017/2018 school year. the level of success of the pree test of students who reached 78 was 15 students and those who scored 78 as many as 14 students with a mean grade of 71, 44 and the percentage of completeness was 51.72%, this means that some students have not been able to master the preparation material. In the first cycle, students who achieved a score of 78 were 16 and those who scored 78 were 13 students with a mean grade of 71.96% and the percentage of learning success was 55.17%. Whereas in the second cycle students who scored ≥ 78 were 26 students and those who scored ≤ 78 were 3 students with a class average value of 83.96 and the percentage of learning success was 89, 65%. Based on the results of the second cycle test, there was an increase in student learning outcomes.Keywords: Think Pair Share learning model, To Improve Learning Outcomes